How additives steer sewage sludge hydrochar properties: Divergent pathways of MgO/CaO versus sawdust in carbon/nutrient fate and magnetism - Chen Zhang; Guo Chen; Qinghai Wang; Huafen Li; Yanan Wan; Guoxin Sun; Ke Wang; Tianshu Chu; Ruilun Zheng (Bioresource Technology, 2026)

A visual balance calculation method for wemaps combining fuzzy clustering and multi-factor driving - Rongjuan Ma; Haowen Yan; Xiaomin Lu; Zhaoyang Hou; Xiaolong Wang; Pengbo Li; Tianshu Chu; Fukang Mao (Earth Science Informatics, 2025)

Increased VOC reactivity forcing ozone pollution in the Yangtze River Delta region, China: Evidence from an eight-year observation at an urban site and implications for future control strategies - Xin Zhang; Miao Ning; Wanghui Chu; Yuanzhou Dong; Xurong Shi; Tianshu Chen; Qiang Ma; Lijuan Wang; Yezheng Wu; Wei Zheng; Zhijun Wu (Journal of Hazardous Materials, 2025)

Coupling use of stable isotopes and functional genes as indicators for the impacts of artificial restoration on the carbon storage of a coastal wetland invaded by Spartina alterniflora, southeastern China - Tianshu Chu; Danyang Li; Yi-Jia Shih; Yuqing Guo; Kai Liu; Fenfen Ji; Jun Li; Yuzhu Yin; Ruohai Chen (Frontiers in Marine Science, 2024)
Coastal wetlands are characterized by high production and thus play an important role in global climate change. In past decades, the invasion of Spartina alterniflora has caused many problems of coastal wetlands in southeastern China, and the restoration of such areas was mainly conducted by replacing Spartina alterniflora with mangrove plants. This may impact the carbon storage dynamics in such areas. In this study, stable isotopes (δ 13 C and δ 15 N) and molecular analysis were used to reveal the impact of artificial restoration on the carbon storage of Quanzhou Bay Estuary Wetland Natural Reserve. The major results are as follows: (1) the change in dominant plants results in a changing major source of soil organic matter, from external sources to mangrove plants; (2) the decrease in soil organic matter following the removal of Spartina alterniflora may be primarily caused by the loss of external organic matter, while the production of mangroves may offset such loss and enhance the content and stability of carbon storage over the long term; (3) microbial CO 2 assimilation may serve as an alternative source of bioavailable carbon and thus support the activity of benthic community. Our results revealed the long-term benefits of such restoration on the carbon storage function of wetlands invaded by Spartina alterniflora . Furthermore, the integrating of isotopic tracers and molecular technology may provide new insights in understanding the response of the carbon storage in coastal areas to human activity.

Humidity sensing based strategy for in situ probing and manipulating electrified interfacial water adsorption dynamics - Tianshu Chu; Xinyuan Mao; Bowei Zhang; Fu-Zhen Xuan (Chemical Engineering Journal, 2023)

miR-146a contributes to atherosclerotic plaque stability by regulating the expression of TRAF6 and IRAK-1 - Tianshu Chu; Xu Xu; Zhimin Ruan; Liyong Wu; Mingli Zhou; Guofu Zhu (Molecular Biology Reports, 2022)

Default mode network integrity changes contribute to cognitive deficits in subcortical vascular cognitive impairment, no dementia - Qi Qin; Yi Tang; Xuejiao Dou; Yida Qu; Yi Xing; Jianwei Yang; Tianshu Chu; Yong Liu; Jianping Jia (Brain Imaging and Behavior, 2021)

miR-155 inhibits oxidized low-density lipoprotein–induced apoptosis in different cell models by targeting the p85α/AKT pathway - Zhimin Ruan; Tianshu Chu; Liyong Wu; Mingguo Zhang; Mei Zheng; Qian Zhang; Mingli Zhou; Guofu Zhu (Journal of Physiology and Biochemistry, 2020)